Legal Interpretation of Obscenity Law Elements and Law Enforcement - Madani, Kurnia Dhita; Agustanti, Rosalia Dika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Obscenity is a criminal act that violates immorality. The judge's verdict is a very important in every process. The definition of obscenity in the judge's verdict often has different meanings. This is considered an obscene act that does not have a limit on the meaning of an act that can be said to be obscene and not. This article aims to examine the elements of obscene acts and the law enforcement. This study uses normative juridical research method, by analyzing existing data and reviewing the data. The results of this study are the regulations that have been in effect are considered not to have elements in more detail. Especially in 289 KUHP has a vital element.that have been in force are considered not to have elements in a more detailed and comprehensive manner. Law enforcement officials must prioritize a sense of justice for victims of sexual abuse in accordance with the actions that have been carried out. In this case, the government cooperates with other relevant agencies to provide counseling regarding the offense of sexual abuse so that people can be more careful and increase their awareness. In addition, it needs to be formulated in the Criminal Code or other regulations regarding obscene acts which have a broad meaningso that they include acts of intercourse. The provision of sanctions by law enforcement officials is also expected to take into account the deterrent effect that will be caused to the perpetrators, this can be done through the provision of maximum sanctions demands.